The Relationship Between Hypertension and Mortality in COVID-19 Patients at Soedirman M. S. Wonogiri Hospital - Devisda Shafiy Anisa; Desie Dwi Wisudanti; Pipiet Wulandari (Warmadewa University, 2025)
According to data from the Ministry of Health of the Republic of Indonesia, there were 6,103,533 confirmed positive cases of COVID-19, with 156,776 deaths. One factor contributing to the high mortality rate of COVID-19 is the presence of comorbidities. Hypertension and diabetes mellitus are the most common comorbidities found in COVID-19 patients. In cases of hypertension, the SARS-CoV-2 virus can interfere with blood pressure regulation, resulting in sustained increases in blood pressure in infected patients. If this condition is not managed, organ damage may occur and worsen the patient’s clinical status. This study aims to evaluate the effect of comorbid hypertension on the mortality of COVID-19 patients at dr. Soediran M. S. Wonogiri Hospital. This research employed an analytical observational method with a cross-sectional design. Medical record data from 94 COVID-19 patients, consisting of 47 patients with hypertension and 47 patients without hypertension, were analyzed using the Chi-square test. The highest age distribution among COVID-19 patients was in the 51–60-year age group (21.3%). The results showed a significant association between comorbid hypertension and mortality in COVID-19 patients (p = 0.001), with an RR value of 1.27. COVID-19 patients with comorbid hypertension were 1.27 times more likely to die than those without hypertension. This study provides a better understanding of health risks in COVID-19 patients with comorbid hypertension and may assist in developing more effective health policies.